2022
DOI: 10.3892/ol.2022.13657
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA PVT1 promotes the proliferation, migration and EMT process of ovarian cancer cells by regulating CTGF

Abstract: Ovarian cancer remains one of the most common gynecological malignancies with a poor prognosis. The present study investigated the roles of long non-coding RNA plasmacytoma variant translocation 1 (lncRNA PVT1) in the regulation of the malignant phenotype of ovarian cancer cells, including cell proliferation, migration, invasion and epithelial-mesenchymal transition (EMT). SKOV3 and CAOV3 cells were transfected with small interfering RNA (siRNA) targeting lncRNA PVT1 (si-PVT1) or control siRNA and the si-PVT1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The lncRNA, PVT1, has been shown to facilitate EMT by physically interacting with activated STAT3, which then enhances STAT3 binding to the Slug promoter, increasing Slug expression to facilitate EMT (54). Indeed, several studies have revealed that PVT1 is an EMT inducer (52,53,(184)(185)(186)(187). Furthermore, STAT3 was also shown to upregulate PVT1 expression through binding to its promoter (14) and therefore, PVT1 and STAT3 form a positive regulatory loop to enhance cancer progression.…”
Section: Lncrnas and The Stat3-emt Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA, PVT1, has been shown to facilitate EMT by physically interacting with activated STAT3, which then enhances STAT3 binding to the Slug promoter, increasing Slug expression to facilitate EMT (54). Indeed, several studies have revealed that PVT1 is an EMT inducer (52,53,(184)(185)(186)(187). Furthermore, STAT3 was also shown to upregulate PVT1 expression through binding to its promoter (14) and therefore, PVT1 and STAT3 form a positive regulatory loop to enhance cancer progression.…”
Section: Lncrnas and The Stat3-emt Axismentioning
confidence: 99%
“…Plasmacytoma variant translocation 1 (PVT1) is a well-studied lncRNA that is located at the 8q24.21 region near the c-Myc oncogene. PVT1 is upregulated by copy number amplification and is able to promote cancer progression ( 52 , 53 ). Zhao et al ( 54 ) showed that PVT1 enhances STAT3 recruitment to the Slug promoter, and transcriptionally enhances Slug expression in gastric cancer.…”
Section: Role Of Stat3 Signaling In Emtmentioning
confidence: 99%
“…The authors suggested that this lncRNA promotes OC cell proliferation, metastasis, and EMT via sponging miR-140-3p and thus increases SNAI2 expression [ 67 ]. Plasmacytoma-variant translocation 1 (PVT1) enhanced the proliferative and migrative potential of OC cells through the modulation of the expression of connective tissue growth factor (CTGF), which in turn also promotes the EMT process [ 69 ]. Moreover, SNHG17 knockdown was found to repress EMT in OC cells via the regulation of miR-485p/AKT1 axis [ 71 ].…”
Section: Regulation Of Emt By Long Non-coding Rnas In Ovarian Cancer:...mentioning
confidence: 99%